Game system for learning using Unity2D - Ho, Chloe Zi Ying (Nanyang Technological University, 2023)
The key aim of this project is to develop a game that seeks to gamify learning while incorporating learning analytics. This project consists of two applications – Space Odyssey, a game for students, and a teacher web application, for teachers to manage learning content. Space Odyssey is a space-themed game where students can visit different planets in various galaxies. As they free-roam the map, they will encounter enemies whom they must battle. The battle involves answering questions related to different academic topics which are set by teachers. Space Odyssey has multiple features including a leader board, achievements tracking and a review function for students to learn from previous mistakes. The teacher web application allows teachers to modify and set questions for the game. At the same time, learning analytics is performed on user data from the game and visualised on the teacher web application, so teachers can track the performance of students.